Tindak Pidana Penipuan dalam Penjualan Tanah yang Terikat Hak Tanggungan - Sunaryo (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
As a state based on the rule of law, Indonesia guarantees the protection of its citizens' rights, including in land sale transactions. Problems arise when land that is still encumbered with a security right (Hak Tanggungan) is sold without the creditor’s consent. Such an act may be classified as a criminal offense of fraud. Victims of this crime are entitled to legal protection under Article 378 of the Indonesian Criminal Code as the general provision, as well as Articles 383 and 385 as the specific provisions.